Most propable number (MPN) and antibiotic resistance pattern of Escherichia coli from smoked Asian Clam, Corbicula fluminea - Priya Darshini Kanniappan (2015)
Up to date, there is not much database regarding the total amount of coliform bacteria isolated from the smoked Asian Clam (Corbicula fluminea) in Malaysia. This study was carried out to provide information about the total number of coliform bacteriapresent in this smoked Asian Clam as well as the antibiogram of the Escherichia coli isolated from the smoked Asian Clam. This information can be useful for future studies for clinical analysis as well as for public health management. The total coliform bacteria were determined using the Most Probable Number (MPN) method and Location A had 28/mL while Location B had >1100/mL of total coliform bacteria present. Confirmation test was done by swabbing the broth from the test tube onto the Eosin Methylene Blue agar and is incubated for 24 H(s). The Completed test was done by inoculating the metallic green colony on lactose broth to confirm the gas produced after 24 H(s) and by using Gram's staining method to determine the isolates are Gram negative. The multiple antibiotic resistance (MAR) of the smoked Asian Clam was 0.57. Results indicated the samples were under high risk exposure to the tested antibiotics. The antibiotic susceptibility test of the smoked Asian Clam to 17 different antibiotics showed that 57.02% were resistant, 6.78% were intermediary sensitive, and 36.2% were sensitive. Overall, the study has shown that the smoked Asian Clam samples from Location A is safe for human consumption whereas samples from Location B were highly contaminated by coliform bacteria and is unsafe for the human consumption according to WHO and EC Directive standards.